Spin- and Angle-Resolved Spectroscopy and Spin Waves in Biogenic Magnonic Systems - Kalejaiye, Akorede (My University, 2021)
This review paper covers aspects of spin waves excitation and propagation as magnons (a quasiparticle of excited spin waves analogous to phonons and plasmons which are also quasiparticles of quanta of vibrational waves and electromagnetic waves propagating along a metal surface respectively) how they can be biologically engineered for applications and probing the biogenic magnonic nanoparticle using lab-scale spin and angular resolved photoemission spectroscopy to obtain more details on spin waves.
Keywords: antiferromagnetic magnons; magnetic metamaterial; magnetotactic bacteria; magnons spin and angle resolved photoemission spectroscopy; spin waves